Percutaneous Intervention of Left Main Coronary Artery Chronic Total Occlusion - Kantaria, Murman; Agladze, Vazha; Machavariani, Pavle; Buleishvili, Maka; Otarishvili, Nino; Sagirashvili, Ekaterine; Sanikidze, Tamar (Journal of Clinical Case Reports and Images, 2019)
Chronic total occlusion (CTO) of the left main coronary artery (LMCA) is rare on the angiograms; Coronary Artery Bypass Grafting is the standard method of its revascularization. To demonstrate that PCI may in some cases be a safe option for patients with a high-risk surgical category, we report a complex clinical case of revascularization of chronic total occlusion of the LMCA, left anterior descending artery (LAD), and circumflex artery (CX). Methods Recanalization of the occluded LMCA and LAD was performed by utilizing the support-balloon technique, and CTO wires (Miracle 3™ wire, Abbott Vascular; Runthrough® NS Intermediate wire, Terumo); LAD, CX, LMCA, and its bifurcation, were stented with 3 drug-eluting stents (Resolute Integrity DES, Medtronic); the "Culotte Stenting " technique was used for bifurcation stenting, followed by "Kissing Balloon" post-dilatation technique; proximal optimization technique was performed in the LMCA. Results The intervention ended without complications. 2 months after stenting, the ejection fraction increased from 20% to 38%, improved almost all parameters of the heart, Congestive Heart Failure functional class decreased to class I. Conclusions It should be considered that LMCA CTO lesions can be successfully revascularized with PCI in case of the selection of the suitable patient and appropriate revascularization technique.
Keywords: Chronic Total Occlusion; Left Main Coronary Artery; Coronary Artery Disease; Culotte Stenting; Percutaneous Coronary Intervention; Drug-Eluting Stents